DEVELOPMENT AND EVALUATION OF GASTRIC FLOATING TABLETS OF RIBOFLAVIN USING BOX-BEHNKEN DESIGN - SVN, PADMA; PAPPULA, NAGARAJU; NAIK, V. VASU; MURTHY KOLAPALLI, VENKATA RAMANA (International Journal of Applied Pharmaceutics, 2023)
Objective: To develop and evaluate gastric floating tablets of riboflavin that was thermally fused using an experimental design method. Methods: Gastric floating tablets were developed using the Box-Behnken design. The effect of sintering on various tablet properties is assessed. The prepared floating tablets were tested for characteristics like usual tablet quality control tests with special emphasis on buoyancy studies and in vitro drug release studies. Results: The drug-excipient incompatibility studies indicated no interactions between riboflavin and carnauba wax. Sintering the powder at 1200, °C partially decreased its crystallinity and improved drug release for up to 16 h. The tablets demonstrated good flow properties, acceptable hardness, low friability, and uniformity in thickness and diameter. Statistical models successfully optimized the formulation to achieve desired characteristics and practical compressibility. The optimal amounts of the variables, according to Design Expert® 12 software, were 59.19 mg of carnauba wax, 14.63% w/w of sodium bicarbonate, a sintering temperature of 74.68 °C, and a sintering exposure time of 1.99 h. Conclusion: In vitro dissolution studies were conducted on the optimized formulation to verify the model's predictions. The experimental results closely matched the predictions. The optimized formulations showed a floating lag time of 104 seconds and a floating duration of 12.3 h. The obtained T90 was found to be 11.3 h which followed zero order kinetics with a non-Fickian diffusion mechanism.